Non-Representational Theory and the Creative Arts - Boyd, Candice P.; Edwardes, Christian; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Palgrave Macmillan, 2019)
This book presents distinct perspectives from both geographically-oriented creative practices and geographers working with arts-based processes. In doing so, it fills a significant gap in the already sizeable body of non-representational discourse by bringing together images and reflections on performances, art practice, theatre, dance, and sound production alongside theoretical contributions and examples of creative writing. It considers how contemporary art making is being shaped by spatial enquiry and how geographical research has been influenced by artistic practice. It provides a clear and concise overview of the principles of non-representational theory for researchers and practitioners in the creative arts and, across its four sections, demonstrates the potential for non-representational theory to bring cultural geography and contemporary art closer than ever before.
Acknowledgments -- Notes on Contributors -- Foreword: Non-Representational Dreams -- 1 Creative Practice and the Non-Representational -- Part 1 Situated Practices in Art, Craft and Design -- 2 Geo/graphic Design -- 3 Geologic Landscape: A Performance and a Wrecked Mobile Phone -- 4 Micro-Geographies of the Studio -- 5 Making, Knowing and Being Made: Hand-Stitching Beyond Representation -- 6 Feeling Queer Art in Public: The Gay Liberation Monument -- Part 2 Artistic Engagements with Geography -- 7 Affecting Objects: Enacting Gesture within a Performative Research Enquiry -- 8 Circadian Rhythms, Sunsets, and the Representational Thresholds of Time-Lapse Photography -- 9 'Call That Art? I Call It Bad Eyesight': Seeing or Not Seeing in the Context of Responsive Art Practice -- 10 Forward, Back, Together - and the Materialities of Taking Part -- 11 Where Does 'Your' Space End and the Next Begin? Non-Representational Geographies of Improvised Performance -- Part 3 Geographers Exploring Artistic Practice -- 12 Making Theatre That Matters: Troubling Subtext, Motive, and Intuition -- 13 Creativity, Labour, and Captain Cook's Cottage: From Great Ayton to Fitzroy Gardens -- 14 Material Conditions in the Post-Human City -- 15 Attuning to the Geothermal-Urban: Kinetics, Cinematics, and Digital Elementality -- 16 Thresholds of Representation: Physical Disability in Dance and Perceptions of the Moving Body -- Interlude: Supervising -- Part 4 Sound, Music, and Creative Mobilities -- 17 Audio Recording as Performance -- 18 Psy(co)motion: Anti-Production and Détournement in Affective Musical Cartographies -- 19 Walk with Me -- 20 Imaginal Travel: An Expedition in Fine Art Practice in Search of the Loneliest Palm -- 21 Fragments (formerly Tales from the Asylum) -- 22 On Edge: Writing Non-Representational Journeys -- Afterword: Sensing the World Anew.
Keywords: Human geography; Performing arts; Theater; Arts; Human Geography; Theatre and Performance Arts; Arts